2016
DOI: 10.1590/s0100-204x2016001100005
|View full text |Cite
|
Sign up to set email alerts
|

Agronomical performance of 'Piemonte' mandarin grafted on several rootstocks in the Brazilian Coastal Tablelands

Abstract: -The objective of this work was to evaluate the agronomical performance of 'Piemonte' mandarin grafted on 11 rootstocks grown under the edaphoclimatic conditions of the Coastal Tablelands, in the state of Sergipe, Brazil. The following combined agronomical parameters were evaluated: vegetative growth, abundance of phytophagous mites, plant yield, drought tolerance, and physicochemical quality of fruit. 'Piemonte' mandarin had the best productive performance when grafted on 'Santa Cruz Rangpur' lime, 'Red Rough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
3
13
0
1
Order By: Relevance
“…Cerqueira et al (2004) reported that HTR -051 has good results when it undergoes a period of water deficit followed by hydration, whereas the 'Orlando' tangelo, the 'Swingle' citrumelo and the 'San Diego' citrandarin show lower water deficit tolerance in this period. It corroborates results on the 'Swingle' citrumelo and the 'Orlando' tangelo, which are less tolerant to drought (PRUDENTE; SILVA; CUNHA CUNHA SOBRINHO et al, 2013;CARVALHO et al, 2016a).…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…Cerqueira et al (2004) reported that HTR -051 has good results when it undergoes a period of water deficit followed by hydration, whereas the 'Orlando' tangelo, the 'Swingle' citrumelo and the 'San Diego' citrandarin show lower water deficit tolerance in this period. It corroborates results on the 'Swingle' citrumelo and the 'Orlando' tangelo, which are less tolerant to drought (PRUDENTE; SILVA; CUNHA CUNHA SOBRINHO et al, 2013;CARVALHO et al, 2016a).…”
Section: Resultssupporting
confidence: 82%
“…The ones grafted on both hybrids LVK x LCR -010 and TSKC x CTTR -002 and on the 'Cravo Santa Cruz Rangpur' lime had the highest level of drought tolerance (DT), followed by those grafted on 'Indio' and 'Riverside' citrandarins, 'Red Rough' lemon, 'Sunki Tropical' mandarin and on the hybrid HTR -051. Carvalho et al (2016a) found similar results of high level of DT conferred by rootstocks LVK x LCR -010 and 'Cravo Santa Cruz Rangpur' lime to the 'Piemonte' mandarin ['Clementina' mandarin (C. clementina hort. ex Tanaka) x tangor (C. sinensis x C. reticulata Blanco) 'Murcott'].…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations